A Sharia Perspective on E-Commerce Affiliate Marketing in Indonesia: A Study of Shopee Marketplace - Najib, Ainun (Prophetic Law Review, 2024)
Traditional face-to-face marketing has evolved significantly since the advent of online systems, leveraging technological advancements to create new models like affiliate marketing. Affiliate marketing has become increasingly prevalent in Indonesia, particularly within e-commerce platforms such as Shopee. As these modern marketing practices expand, ensuring that Islamic values are upheld in their implementation becomes crucial. This calls for a thorough examination of affiliate marketing through the lens of Islamic law. This research, based on a normative legal research methodology, explores the alignment of affiliate marketing practices with the principles of Islamic economic law, specifically scrutinizing the collaboration between Shopee and its affiliate participants. It is found that affiliate marketing, as practiced by Shopee, can be considered permissible under Islamic law, provided that certain conditions are met. The commission-based model employed by Shopee, and its affiliates closely mirrors the contracts of samsarah (brokerage) and wakalah bil ujrah (agency with a fee) in Islamic commercial law. These contracts ensure that the transactions comply with Islamic principles' ethical and legal framework, promoting fairness, transparency, and mutual consent.